Filogeografia de anfíbios anuros dos campos subtropicais do sudeste da América do Sul - Alves, Suélen da Silva (2019)
The climatic and geological events of the Neogene period and the climatic fluctuations of the Quaternary have been pointed out as the main responsible for the diversification of the biota in open areas of South Am erica. However, little is known about phylogeographic patterns of anurans in the grasslands of this region and how these grassland ecosystems shaped the diversity of the anurofauna. In this sense, the general objective of th is T hesis was to investigate th e phylogeographic pattern of multiple anuran species with different life histories and co distributed in the subtropical grasslands of southeast ern South America. The T hesis was divided into two chapters, accordi ng to the specific objectives: (1) to access genetic diversity, patterns of population and historical demographic structuring, and to test temporal congruence o n the demographic pattern ; (2) to reconstruct the phylogenetic relationships, to test the temporal congruence in the divergence pattern , to r econstruct the phylogeographic diffusion pattern in space and time and, finally, to perfor m the species delimitation . The species selected are distributed in three basic geographic patterns: widely distributed throughout the open and forest vegetation of S outh America, species distributed throughout the Pampa grasslands and Highland grasslands of the Atlantic Forest biome and species restricted to the Pampa grasslands . We sequenced a fragment of the 16S gene from 371 samples of six nominal species of anura ns Leptodactylus latrans, Physalaemus cuvieri, Scinax uruguayus, Physalaemus gracilis, Phyllomedusa iheringii , and Pseudis minuta )), along their geographical distributions. We found that diversification processes in this region are complex and that the spe cies associated with grasslands areas present variable responses. We recovered from high to low genetic diversity, species with and without phylogeographic structuring and demographic histories with some peculiarities, but congruent in their majority. Most grassland anuran lineages showed signs of population expansion during the Quaternary glacial cycles and four of these lineages in population expansion had an expansion pulse at the same evolutionary time (synchronic), while one species had a p ulse expans ion at a random time . These coexpansion and expansion pulses coincide d with the climatic dynamics of Pliocene Pleistocene, i.e. e., Neogene Quaternary. In addition, our paleodistribution models were congruent in demonstrating a positive relation of the specie s distribution with the Last Glacial Maximum (LGM ). We report a strong geographic structure, high genetic divergence and a high number of mutational stages between clades of two typically grassland anuran species. We recover a deep divergence dating back t o the Oligocene and phylogeographic breaks of the major clades dating from the Miocene, but not temporally congruent. In addition we report a continuous dive rsification during the Pliocene Quaternary with increase of dispersion of these lines during the Quaternary. Finally, we delineate five coalescing lineages under the name of two typically grassland anuran species S uruguayus and P gracilis )). It is probable that the Miocene marine transgressions are responsible for the initial diversification of the se lineages and that the climatic and grassland dynamics together with the topography of the region have contributed to shape the present diversity and distribution of these species, evidencing a strong interaction between paleogeogr aphic and paleoclimatic forces. This is the first study with comparative phylogeography of anurans in the subtropical grasslands of southeast ern South America.